The Effectiveness of Education and Training (DIKLAT) on Android-Based Digital M arketing in the Development of M arketing for PKK Karangdowo's Batik Micro Small and M edium Enterprises (MSMEs) - Rohman, Mamo’ Abdul; Sudiyanto, Sudiyanto; Santosa, Eka Budhi (Universitas Sebelas Maret, 2023)
Micro Small and Medium Enterprises (MSMEs) are businesses or enterprises conducted by individuals, groups, small business entities, or households. Similarly, the TP PKK (Family Welfare Movement) of Karangdowo Village also has MSMEs, specifically in the form of batik production. Although the batik production in these MSMEs is of good quality, the sales still fall short of expectations. Therefore, there is a need for training in digital mark eting techniques. This research aims to provide an explanation regarding the effec-tiveness of digital marketing training conducted by MSMEs of PKK Ka-rangdowo in increasing the sales of PKK Karangdowo's batik products. The research subjects are 10 PKK mothers selected through a purposive sampling technique. The research method used is an experimental one, collecting questionnaire data from the pre-test and post-test phases. Data analysis is conducted using descriptive statistics. This method explains how the effec-tiveness of digital marketing training contributes to the increase in sales of batik products owned by PKK Karangdowo's MSMEs. The results of the re-search indicate that digital mark eting training can enhance the sales of MSMEs' batik products compared to previous sales. Based on these results, it can be concluded that the marketing strategy development carried out by MSMEs of PKK Karangdowo, through the implementation of digital market-ing training, is considered successful in increasing the sales figures of their batik products.